Analisis Reaktifitas IMLTD Donor Pengganti dan Sukarela di UPD RSUD Provinsi NTB - Arie Afianthara; Menap Menap; Lalu Abdul Khalik (Universitas Malahayati Lampung, 2026)
ABSTRACT This analytical retrospective study examined comprehensive data of 12,610 blood donors who donated at the Regional General Hospital Blood Transfusion Unit in West Nusa Tenggara Province during a six-month period from July 1 to December 31, 2025. The research was designed with primary objectives to map complete demographic and biological profiles, identify temporal donation patterns throughout the observation period, and compare IMLTD screening results between replacement donor group comprising 72 percent and voluntary donor group comprising 28 percent. Research methodology employed total sampling approach with descriptive statistical analysis for profile characterization, chi-square testing for bivariate association exploration, and multivariate logistic regression for identification of independent predictors. Research findings demonstrated that IMLTD reactivity in replacement donors reached 2.50 percent (227 out of 9,079 donors) which was significantly higher compared to voluntary donors at 0.91 percent (32 out of 3,531 donors) with p-value less than 0.001 and risk ratio 2.78. Hepatitis B represented the dominant component with disparity of 1.80 percent versus 0.54 percent. Replacement donor status, age greater than 40 years, and first-time donor status were identified as significant independent predictors. The study recommends systematic transition toward voluntary donor system through phased strategies based on local empirical evidence. Keywords: Replacement Donor, IMLTD Reactivity, Voluntary Donor System. ABSTRAK Penelitian retrospektif analitik ini menganalisis data komprehensif sebanyak 12.610 donor darah yang melakukan donasi di Unit Pengelola Darah Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat selama periode enam bulan dari 1 Juli hingga 31 Desember 2025. Penelitian ini dirancang dengan tujuan utama memetakan profil demografis dan biologis lengkap, mengidentifikasi pola donasi temporal sepanjang periode observasi, serta membandingkan hasil skrining IMLTD antara kelompok donor pengganti yang mendominasi sebesar 72 persen dan donor sukarela sebesar 28 persen. Metodologi penelitian menggunakan pendekatan total sampling dengan analisis statistik deskriptif untuk karakterisasi profil, uji chi-square untuk eksplorasi asosiasi bivariat, dan regresi logistik multivariat untuk identifikasi prediktor independen. Hasil penelitian menunjukkan bahwa reaktifitas IMLTD pada donor pengganti mencapai 2,50 persen (227 dari 9.079 donor) yang signifikan lebih tinggi dibandingkan donor sukarela sebesar 0,91 persen (32 dari 3.531 donor) dengan nilai p kurang dari 0,001 dan risk ratio 2,78. Hepatitis B merepresentasikan komponen dominan dengan disparitas 1,80 persen versus 0,54 persen. Status donor pengganti, usia di atas 40 tahun, dan status donor pertama kali teridentifikasi sebagai prediktor independen signifikan. Penelitian merekomendasikan transisi sistematis menuju sistem donor sukarela melalui strategi berjenjang berbasis bukti empiris lokal. Kata Kunci: Donor Pengganti, Reaktifitas IMLTD, Sistem Donor Sukarela.